FOREIGN EXPERIENCE IN ATTRACTING FOREIGN INVESTMENTS INTO THE NATIONAL ECONOMY - Khoshimov Sabir Murtazaevich (Journals Park Publishing, 2023)
The article examines the role and importance of foreign investment in the socio-economic development of the country, studied international experience in attracting foreign investment into the national economy, and considered conclusions, proposals and recommendations based on international experience.
Keywords: foreign investment, investment attractiveness, foreign direct investment, investment environment, investment policy, investment regime, newly industrialized countries.